Chattering-Free Adaptive Sliding Mode Control for Attitude Tracking of Spacecraft with External Disturbance. (17th March 2014) - Zhang, Xuxi; Liu, Xianping; Zhu, Qidan
Abstract : The attitude tracking problem of spacecraft in the presence of unknown disturbance is investigated. By using the adaptive control technique and the Lyapunov stability theory, a chattering-free adaptive sliding mode control law is proposed for the attitude tracking problem of spacecraft with unknown disturbance. Simulation results are employed to demonstrate the effectiveness of the proposed control design technique in this paper.